Evaluation of ultrasonographic findings in cases with hepatic cirrhosis - Bülent KARA; Nafi YAZICIOĞLU; Belkıs ÜNSAL; Kadir AKSÖZ; Abidin ALTINAY; Günay ÖNDER; Sadun KOŞAY (Turkish Journal of Gastroenterology, 2020)
-